The effects of using diverse vocabulary learning strategies on word mastery: a review - Nasim Mehrabian; Hadi Salehi (Politeknik Negeri Bali, 2019)
In accordance with the belief that language learning strategies are undeniably teachable, several researchers have attempted to expand the knowledge of language learners toward the productive use of learning strategies with the aim of empowering them to gain personal control of these strategies during learning process. The present investigation is an effort to inquire into the connection between using diverse vocabulary learning strategies and word mastery. Many studies have been done in this area. Therefore, some of these related papers were selected and carefully examined. The findings of the previous studies supported the fact that there is a significant and positive correlation between vocabulary knowledge and word learning strategies. The results suggested that training vocabulary learning strategies has positive effect on both language learning and language learners. Moreover, the instruction of strategy comes to the aid of teachers and learners to meet their needs.